Special papersArrhythmogenic right ventricular cardiomyopathy in a 52-year-old man – clinical presentation mimicking an acute coronary syndrome - Zandecki, Łukasz; Sadowski, Marcin; Kurzawski, Jacek; Janion-Sadowska, Agnieszka (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Arrhythmogenic right ventricular cardiomyopathy is an infrequently diagnosed, genetically determined disease that leads to significant clinical consequences, including progressive heart failure and ventricular arrhythmias accounting for sudden cardiac death. We report the case of a 52-year-old patient who presented with ventricular tachycardia and features of an acute coronary syndrome. However, routine tests excluded critical coronary stenosis and the final diagnosis was arrhythmogenic right ventricular cardiomyopathy.